Pengaruh Penggunaan Alat Pelindung Diri (APD) terhadap Pencegahan Risiko Kecelakaan Kerja - Wahyuni, Sri; Lheena, Cut Putri Zaila; Kamalurrijal; Afriliansyah; Zakaria, Radhiah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study evaluates the effectiveness of using personal protective equipment (PPE) in preventing workplace accident risks across high-risk industrial sectors. The systematic review, employing the PRISMA approach, includes cross-sectional studies, meta-analyses, and prevalence evaluations. Results show that consistent PPE use can reduce workplace accident prevalence by up to 60%, although its effectiveness depends on worker compliance, the availability of quality PPE, safety training, and supervision. Factors such as ergonomic PPE design, safety culture, and continuous education were also found to significantly contribute to successful PPE implementation. These findings underscore the importance of a comprehensive approach to implementing workplace safety strategies to foster a safer and healthier.